تأثير المعالجة الحرارية ووسيط التبريد على بعض الخواص الميكانيكية لأنابيب البولي إيثلين عالي الكثافة HDPE - منصور رامي (Latakia University Journal -Engineering Sciences Series, 2019)
يهدف البحث إلى دراسة تأثير المعالجة الحرارية ووسيط التبريد على الخواص الميكانيكية الممثلة بالقيم المميزة لمنحنيات (القوة – الاستطالة) لعينات مقتطعة من أنابيب البولي إيثلين عالي الكثافة المخصصة لمياه الشرب، وقد تمت المعالجة الحرارية وفق النظام التالي: درجات حرارة التسخين ( 100 ,110 ,120 ) C° وأزمنة التسخين ( 1, 3, 5, 6 ) hour. أظهرت نتائج الاختبارات أن أفضل قيم لقوة الخضوع وتشكل العنق والتحطم يتم الحصول عليها عند الدرجة 120 C° وزمن قدره 5 hour، وذلك عند استخدام الهواء كوسيط تبريد، كما أظهرت نتائج الاختبارات أن أفضل وسيط تبريد هو الهواء الطبيعي يليه التبريد القسري بالزيت ثم التبريد القسري الماء. This search aims to study the effect of heat treatment conditions and cooling mediums on mechanicals properties, important values of (Load-Elongation) curves. For these reasons, we prepared many specimens from HDPE pipes for drinking water. The treatment system was the following: Heat treatment temperatures were (100, 110, 120) C° and the times of heating were (1, 3, 5, 6) hours. The results show that we get the best values of force at yield, neck formation and at break after 5 hours heating at 120C° when we use the air like cooling medium, and the best mediums for cooling are at the following: the natural cooling by air, forced cooling by mineral oil then forced cooling by water